1970
DOI: 10.1128/jvi.6.6.782-787.1970
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Basis of the Adenovirus 8-9 Cross-Reaction

Abstract: The dodecon and hexon components of adenovirus types 8 and 9 have been extensively purified for use in establishing the basis of the cross-reaction between these types. Dodecons, the complete hemagglutinins, were purified 304to 362-fold by fluorocarbon extraction, calcium phosphate batch chromatography, and ion-exchange column chromatography. Hexons, the group complement-fixation (CF) antigens, were purified 230to 240-fold by erythrocyte adsorption, ion-exchange chromatography, and exclusion chromatography. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1972
1972
1988
1988

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Schedule 1 was dropped from further study. The results with schedule 3 supported our long-term experience in immunizing rabbits with various AV serotypes by the im route (7,8). It therefore appeared that the im route alone was superior to either iv method previously used.…”
Section: Resultssupporting
confidence: 62%
“…Schedule 1 was dropped from further study. The results with schedule 3 supported our long-term experience in immunizing rabbits with various AV serotypes by the im route (7,8). It therefore appeared that the im route alone was superior to either iv method previously used.…”
Section: Resultssupporting
confidence: 62%
“…Kinetic neutralization of 300 PFU of VS virus was performed as in Fig. 1 and 2. investigators have presented convincing arguments suggesting a multihit requirement for neutralization to occur (4,11,29). Still other studies have concluded that the efficacy of viral neutralization varies with the isotype or avidity of the neutralizing antibody (16).…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen independently isolated hybridomas producing monoclonal antibodies to the glycoprotein of vesicular stomatitis virus were isolated and studied for their capacity to neutralize viral infectivity. By measuring competitive binding of 125ilabeled monoclonal antibodies in a radioimmunoassay, 11 different, non-crossreacting antigenic determinants were identified on the vesicular stomatitis virus G protein. All monoclonal antibodies reacting with determinants 1, 2, 3, and 4 resulted in viral neutralization, whereas those binding to the other seven determinants did not neutralize infectivity.…”
mentioning
confidence: 99%
“…Neutralising antibody is directed largely at the hexons, whilst anti-penton serum has only weak neutralising activity and anti-fibre serum hardly any at all (Kjellen and Pereira, 1968). Although anti-penton serum has low neutralising activity, it considerably enhances the neutralising effect of anti-hexon antibody (Hierholzer and Dowdle, 1970) and furthermore anti-penton serum alone can have a significant neutralising capacity on the addition of antiglobulin (Norrby and Wadell, 1972). This suggests that critical sites are not confined to hexons alone and that maximal neutralisation reactions involve antibody reactions at more than one site.…”
Section: Mechanism Of Neutralisationmentioning
confidence: 99%